PERFORMANCE DYNAMICS AND JOB SATISFACTION IN HUMAN RESOURCE MANAGEMENT AT PT RLGLOW JAYA ABADI MOJOKERTO CITY - Wibowo, Widya Nila Ari; Dwi Dewianawati; Nindya Rizkawati (Journal of Innovation Research and Knowledge, 2025)
This study aims to provide an in-depth analysis of the influence of human resource management (HRM) policies on job satisfaction and employee performance at PT RLGLOW Jaya Abadi, Mojokerto City. The research employed a qualitative descriptive approach using in-depth interviews with four key informants: production staff, manager, warehouse supervisor, and HRD officer. The collected data were analyzed thematically by considering the dynamics of employee performance within the context of changes in the business environment, particularly in the e-commerce- based industry. The findings reveal that HRM policies such as the implementation of varied reward systems, flexible working hours, open communication channels, and technical training support have significantly increased employee motivation, loyalty, and sense of appreciation. Furthermore, external dynamics such as sales fluctuations due to promotional events and market changes also influence work enthusiasm, to which management responds by adjusting policies and operational strategies. These results emphasize that the combination of adaptive HRM policies and a conducive work environment plays a crucial role in achieving optimal performance and sustaining job satisfaction over time.